PENGARUH KUALITAS SISTEM INFORMASI AKUNTANSI TERHADAP KEPUASAN NASABAH PENGGUNA APLIKASI PEGADAIAN DIGITAL CABANG RAPPANG - Salsabila; Adam Latif; Andi Riska Andreani Syafaruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of accounting information system quality on customer satisfaction among users of the Pegadaian Digital Application at the Rappang Branch. The background of this study is based on the existence of several system issues, such as errors, delayed response times, and data inconsistencies, which may reduce user satisfaction. This research employed a quantitative method with a descriptive approach. The sample consisted of 90 respondents selected from a population of 886 customers using a random sampling technique. Data were collected through observation, questionnaires, documentation, and literature study, and were analyzed using simple linear regression with the assistance of SPSS version 27.The results indicate that the quality of the accounting information system, which includes adaptability, availability, reliability, response time, and usability, is categorized as good. Customer satisfaction is also categorized as good. The regression analysis shows a correlation coefficient (R) of 0.942, indicating a very strong relationship, and a coefficient of determination (R²) of 0.887, which means that accounting information system quality contributes 88.7% to customer satisfaction. Therefore, it can be concluded that the quality of the accounting information system has a positive and significant effect on customer satisfaction. This study is expected to contribute to the development of accounting information systems knowledge and serve as a reference for Pegadaian in improving the quality of its digital services.